Delayed volatiles release phenomenon at higher temperature in TGA via sample encapsulation technique - Ng, Andrew Kay Lup; Abnisa, Faisal; Daud, Wan Mohd Ashri Wan; Aroua, Mohamed Kheireddine (Elsevier, 2018)
Thermogravimetric analysis (TGA) for solid-gas reactions is well formalized and of ubiquitous use. However, the use of volatile samples in TGA often results in pre-loss of volatile sample by evaporation prior to reaching the specified thermal conditions of analysis. Therefore, sample encapsulation method was proposed as an innovative technique to address this issue. This technique was shown to provide a continuous and delayed release of vaporized samples over the range of elevated temperature through the progressive loosening of the hermetic seal of metal capsule. This effect can be enhanced by using capsule with higher material hardness and smaller surface area for sample evaporation. Application of this method in catalytic phenol reduction has shown an increase in benzene yield from 19.2 mol% to 46.5 mol% when phenol is encapsulated by tin cylinder. Based on these findings, delayed volatiles release phenomenon may lead to further opportunities in the area of thermochemical kinetics study for fuel processing such as gasification, carbonization, reforming or petrochemical reactions that involve catalyst activation at high temperature and use of volatile samples such as fuel model compounds in TGA setup.